PEDAGOGICAL PRACTICE AND INCLUSIVE EDUCATION POLICY IN SPECIALIZED EDUCATIONAL SERVICES - Cristina de Medeiros Azevedo, Ana; Amilton da Costa, José; de Cascia da Costa, Francisca; Araújo da Costa, Marluce; Dias Costa, Cleide; Medeiros, Salésia (Revista Gênero e Interdisciplinaridade, 2024)
The article reflects on pedagogical practice and inclusion policies in the contemporary educational context, emphasizing inclusion as a fundamental right for all people with disabilities. The author discusses the need for a less prejudiced and segregationist approach, highlighting the importance of a government commitment to guarantee investments that enable inclusive educational actions. The research also addresses diversity in schools, proposing that they become spaces that welcome and respect differences.